Climate Change and Environmental Sustainability-Volume 3 (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
To cope with the challenges of climate change, it is essential to assess climate-induced impacts and explore possible solutions. Remote sensing techniques are capable of monitoring, collecting, interpreting, and mapping the physical characteristics of Earth’s surface and its associated spatiotemporal variations. These techniques outperform many data acquisition techniques in overcoming spatial and geographic constraints. The adoption of remote sensing techniques strengthens the capacity for climate change mitigation and adaptation and facilitates evidence-based climate governance. This book presents the use of different kinds of remote sensing techniques to obtain original data across global, regional, city, or local scales for exploring climate-related issues such as sea level variation, sea ice dynamics, drought, extreme heat and precipitation, ecosystem services and carbon sequestration, forest and vegetation cover, coastal subsidence, atmospheric carbon monoxide, soil erosion and runoff, and urban heat islands. This book is important to demonstrate the use of remote sensing techniques for revealing climate-related risks and vulnerabilities. Meanwhile, results reported in this book provide a good understanding of the climate emergency situations, drivers, and solutions. We expect the book to benefit decision makers, practitioners, and researchers in different fields such as climate modeling and prediction, forest ecosystem, land management, urban planning and design, urban governance, and institutional operations. Prof. Bao-Jie He acknowledges that Project NO. 2021CDJQY-004 is supported by the Fundamental Research Funds for the Central Universities and that Project NO. 2022ZA01 is supported by the State Key Laboratory of Subtropical Building Science, South China University of Technology, China. We appreciate the assistance from Mr. Lifeng Xiong, Mr. Wei Wang, Ms. Xueke Chen, and Ms. Anxian Chen at the School of Architecture and Urban Planning, Chongqing University, China.